Knowledge of nursing students regarding swine influenza A at the University of Limpopo, South Africa - Mamogobo, P. M. (My University, 2014)
The study describes the knowledge of nursing students with regard to swine influenza A at the University of Limpopo. A qualitative descriptive and contextual design was used to describe the knowledge of nursing students regarding the swine influenza A at the University of Limpopo, South Africa. The population comprised all third year nursing students at the University of Limpopo’s School of Health Sciences. Purposive sampling was used to select participants from amongst third level nursing students. Semi-structured interviews with a guide and an audiotape were used to collect data until saturation was reached. Data were analysed qualitatively using open coding method. The study revealed three major themes with sub-themes regarding knowledge, perceptions about influenza A (H1N1) virus and precautionary measures to prevent the spread of the virus. It is recommended that strategies to improve knowledge of nursing students with regard to swine influenza A (H1N1) should be developed.
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) Supplement 1:2 (June), 2014, pp. 413-423.
Keywords: Swine influenza A (H1N1); Nursing students; Nurses -- South Africa